2005
DOI: 10.1017/s0265021505001092
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fluid responsiveness in mechanically ventilated cardiac surgical patients

Abstract: The results of our study suggest that stroke volume variation and its surrogate pulse pressure variation derived from pulse contour analysis using an improved algorithm can serve as indicators of fluid responsiveness in normoventilated cardiac surgical patients. Whenever changes in systemic vascular resistance are expected, the PiCCO plus system should be recalibrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 31 publications
2
72
2
4
Order By: Relevance
“…In this review, we adopted the modified 19-point STARD score to judge the quality of the investigation in the selected studies (Table 1). Each criterion was assigned one point and the overall score divided into categories: poor (score 0-10), adequate (11)(12)(13)(14)(15) and good (16)(17)(18)(19). The results of the selected studies were not metaanalysed due to the heterogeneity in methodologies, patient populations, modes of mechanical ventilation, definitions of fluid responsiveness and volume of fluid challenges given.…”
Section: Methodsmentioning
confidence: 99%
“…In this review, we adopted the modified 19-point STARD score to judge the quality of the investigation in the selected studies (Table 1). Each criterion was assigned one point and the overall score divided into categories: poor (score 0-10), adequate (11)(12)(13)(14)(15) and good (16)(17)(18)(19). The results of the selected studies were not metaanalysed due to the heterogeneity in methodologies, patient populations, modes of mechanical ventilation, definitions of fluid responsiveness and volume of fluid challenges given.…”
Section: Methodsmentioning
confidence: 99%
“…In the past decades, it has been shown that static indices such as CVP, PCWP, left ventricular end diastolic area, and right ventricular end-diastolic volume are not accurate for the prediction of fluid responsiveness [13,[47][48][49][50][51]. In contrast, several studies have shown that dynamic indices, such as SVV and PPV, are able to predict fluid responsiveness accurately [52][53][54][55][56].…”
Section: Pulse Contour Analysismentioning
confidence: 99%
“…연속적 자동 맥압변이의 안전성 및 유효성 평가에 선택된 문헌은 총 20편으로 연구유형은 모두 진단법 평가연구였다 (Table 3) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. [정리: 편집위원회]…”
Section: 체계적 문헌고찰 및 메타분석 결과unclassified